Variations of the submental artery: A series of cases - Adarsh Kudva; Vedushi M. Jain; Ujwal K. Malladi; Krishnaraj Somayaji (Oral Oncology Reports)
This article aims to educate surgeons about the variations in the course of the submental artery that exist and are encountered when performing routine head and neck dissection. Vascular architecture is critical for ensuring the success of regenerative and reconstructive procedures. The authors briefly describe variations in the submental artery that were identified and documented in relation to the mylohyoid muscle during routine neck dissection. It is imperative to understand Submental Artery: its branches, distribution, course and variations that are reported. A clear understanding of the variations will help surgeons maintain the vascularity of flaps.